The Effect of Internal Factors on Performance Measurement in Indonesian Local Government - Siti Nur Kholishoh; Khoirul Aswar (Information Management and Business Review, 2022)
This study is motivated by the many problems found in performance measurement, especially in district/city governments in Indonesia. This study aims to examine the influence of internal factors, namely the participation of internal stakeholders, internal political support, and the organizational capacity of local government on performance measurement. The data for this study was gathered via a Google form, with 43 questionnaires addressed to the secretary and head of Serang City's program, evaluation, and reporting subdivision. Purposive sampling was used in this investigation, which took a quantitative approach. Structural Equation Modeling (SEM) with Smart Partial Least Square version 3.0 was used as an analytical technique. The results of this study indicate that internal stakeholder participation and the organizational capacity of local government have no significant effect on performance measurement. Internal political support has a significant effect on performance measurement. Meanwhile, the results of this study have several implications for local governments, especially district/city governments, namely as an evaluation material related to performance measurement at the district/city government level as well as providing information for the State Civil Apparatus (ASN) involved in Government Agency Performance Accountability Reports (LAKIP) to always improve their skills in measuring performance and paying attention to the outcomes to be achieved.